Design and Development of a Web-Based Virtual UNU Yogyakarta Campus Tour System to Improve Information Accessibility - Ilzam, Ah Irfan Ulil; 'Alim, Mohammad Fattachul; Muhammad, Wifqi Nur; Halimah, Nadiah Nur; Fadila, Aisyah Nur; Arifah, Nur (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Universitas Nahdlatul Ulama (UNU) Yogyakarta has long depended on static 2D photographs and scattered social media content to convey campus conditions — a method that consistently falls short of giving prospective students any real spatial understanding of the campus environment. For students outside Yogyakarta, this means making enrollment decisions based on incomplete visual fragments. This study addresses that gap by designing and building a web-based 360° Virtual Tour system using the Prototyping development method. The system adopts a decoupled architecture: Django REST Framework handles backend data operations, while Next.js — paired with the React Photo Sphere Viewer library — drives the panoramic front-end display. Black Box functional testing confirmed that all eight tested features operated without error. User Acceptance Testing (UAT) conducted with 66 respondents produced a feasibility score of 83.0%, classified as